Enhanced Extracellular Transfer of HLA-DQ Activates CD3+ Lymphocytes towards Compromised Treg Induction in Celiac Disease - Hudec, Michael; Juříčková, Iva; Riegerová, Kamila; Ovsepian, Saak V; Černá, Marie; O'Leary, Valerie Bríd (International journal of molecular sciences, 2022)
Celiac disease (CeD) manifests with autoimmune intestinal inflammation from gluten and genetic predisposition linked to human leukocyte antigen class-II (HLA-II) gene variants. Antigen-presenting cells facilitate gluten exposition through the interaction of their surface major histocompatibility complex (MHC) with the T cell receptor (TCR) on T lymphocytes. This fundamental mechanism of adaptive immunity has broadened upon recognition of extracellular exosomal MHC, raising awareness of an alternative means for antigen presentation. This study demonstrates that conditioned growth media (CGM) previously exposed to monocyte-derived dendritic cells from CeD significantly downregulates the CD3+ lineage marker of control T cells. Such increased activation was reflected in their elevated IL-2 secretion. Exosome localization motif identification and quantification within HLA-DQA1 and HLA-DQB1 transcripts highlighted their significant prevalence within HLA-DQB1 alleles associated with CeD susceptibility. Flow cytometry revealed the strong correlation between HLA-DQ and the CD63 exosomal marker in T cells exposed to CGM from MoDCs sourced from CeD patients. This resulted in lower concentrations of CD25+ CD127- T cells, suggestive of their compromised induction to T-regulatory cells associated with CeD homeostasis. This foremost comparative study deciphered the genomic basis and extracellular exosomal effects of HLA transfer on T lymphocytes in the context of CeD, offering greater insight into this auto-immune disease.
Keywords: exosome; T-Lymphocytes, Regulatory; alely; celiakie; major histocompatibility complex II; HLA-DQ antigeny; gluteny; Glutens; regulační T-lymfocyty; Humans; gluten; Alleles; monocyte-derived dendritic cells; Celiac Disease; HLA-DQ Antigens; lidé; autoimmunity